Strangers at the Gate : the 'Boat People's' First Ten Years in Canada. (University of Toronto Press, 1999)
Twenty-seven million people in the world are refugees. In this book, Morton Beiser puts readers in touch, emotionally and intellectually, with the reality of refugees in Canada. In the process, he dispels key misconceptions about immigrants in this country and reframes central debates on refugee policy. The book describes Beiser's ten-year study of 1,300 Boat People admitted to Canada between 1979 and 1981. It chronicles the former refugees' struggles to learn English, and to establish themselves economically in their new environment and shows that, contrary to popular opinion, they use fewer health and social services than indigenous Canadians. Beiser finds that, although most refugees in most resettlement situations succeed remarkably well, no country, Canada included, offers newcomers the welcome they need and deserve. This remarkable study, with its profoundly human dimension, should be read by all policy-makers in the fields of immigration and social and health services.